Country‐specific differences of age stereotypes towards older hospital staff and their association with self‐efficacy, work ability and mental well‐being. (25th April 2020) - Weber, Jeannette; Tzivian, Lilian; Müller, Andreas; Angerer, Peter
Abstract: Aims: To compare stereotypes towards older workers between hospital staff in Germany and Latvia and to analyse the relationship between those stereotypes and self‐efficacy, subjective work ability and irritation. Design: Cross‐sectional study. Methods: In 2018, hospital staff, including nurses, physicians and other professions, of two German and three Latvian hospitals were asked to complete the standardized study questionnaire on subjective work ability, occupational self‐efficacy, irritation and stereotypes towards older workers. In the latter scale older workers were defined as ≥45 years of age and the scale ranged from 27–135 whereby higher values reflect higher levels of positive stereotypes. To analyse the relationship between stereotypes and those work‐related outcomes, multiple linear regression models, including interaction terms between stereotypes and age, were built and adjusted for occupational group, sex and country. Results: Data from 300 employees of Latvian and from 113 employees of German hospitals were included in the analyses. Hospital staff in Germany reported higher levels of positive stereotypes (mean = 87.46, SD 10.04) than hospital staff in Latvia (mean = 84.69, SD 10.10; t (411) = −2.496, p  = .013). When analysing the entire sample of hospital staff in Germany and Latvia, a more positive view on older workers was associated with higher self‐efficacy ( β  = 0.136, p  = .008) and subjective work ability ( β  = 0.063, p  < .001) and lower levels of irritation ( β  = −0.191, p  = .017). The association with self‐efficacy and subjective work ability increased in strength by participant's age. Country‐stratified analyses yielded similar results. Conclusion: The results provide first evidence that stereotypes towards older workers of hospital staff may differ between different European countries. Furthermore, they suggest that counteracting negative stereotypes towards older workers may help to improve self‐efficacy and subjective work ability and reduce irritation levels of older employees. Impact: Those findings emphasize the importance of age stereotypes when examining and promoting older hospital staffs' self‐efficacy, subjective work ability and irritation in a cross‐national context. Abstract : 目的: 比较德国和拉脱维亚医院职工对年长员工的刻板印象, 分析这些刻板印象与自我效能、主观工作能力和被激怒可能性的关系。 设计: 横断式研究。 方法: 2018年, 对2家德国医院和3家拉脱维亚医院包括护士、医生和其他专业人员在内的医院职工进行主观工作能力、职业自我效能、被激怒可能性和对年长员工的刻板印象进行标准化的调查问卷。对于年长员工的刻板印象, 其被界定为45岁以上, 分数范围介于27‐135之间, 分数越高, 表明积极的刻板印象越高。为分析刻板印象与工作相关结果之间的关系, 建立了多元线性回归模型, 包括刻板印象与年龄之间的交互作用项, 并针对职业组、性别和国家进行相应调整。 结果: 数据来自拉脱维亚医院的300名员工和德国医院的113名员工。德国医院职员的积极刻板印象水平(平均值=87.46, 标准差 为10.04)高于拉脱维亚医院职员(平均值=84.69, 标准差 为10.10; t (411) = −2.496, p =0.013)。在分析德国和拉脱维亚医院的所有职员样本时, 对年长员工的看法约积极, 则自我效能越高( β = 0.136, p =0.008), 主观工作能力越高( β = 0.063, p <0.001), 被激怒的可能越低( β = −0.191, p =0.017)。随着受访者年龄的增长, 自我效能和主观工作能力的相关性会更密切。而国家不同等级的分析也得出类似的结果。 结论: 这一结果首次证明不同欧洲国家对医院年长员工的刻板印象存在不同。此外, 他们还建议, 消除对年长员工的负面刻板印象, 可能有助于提高年长员工的自我效能和主观工作能力, 以及减少被激怒的可能。 影响: 这些研究结果强调了年龄刻板印象在跨国背景下检查和提升医院南漳员工的自我效能、主观工作能力和被激怒可能性方面的重要性。